PERAN GANDA KYAI SEBAGAI ULAMA’ DAN UMARA’: TELAAH KONSEP KENEGARAAN AL-GHAZALI DAN PARADIGMA SEKULARISME MODERN - Saifullah; Madlubur Rhisky; Rahmat Zubandi Thahir; Babun Suharto (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
This article examines the dual role of the kyai as both religious scholar (ulama) and political authority (umara) in contemporary Indonesia. Drawing on conceptual and descriptive-analytic methods, it analyzes al-Ghazali’s classical political theory on the unity of religion and state, contrasting it with modern secularism which advocates for institutional separation between the two. In Indonesia, various kyai have served as public officials—regents, governors, legislators, and ministers—creating a complex interplay between moral-religious legitimacy and administrative-political responsibility. This dual role brings both opportunities and vulnerabilities, such as potential conflicts of interest, misuse of religious symbolism, and shifting public perceptions of pesantren. The presidency of Abdurrahman Wahid (Gus Dur) serves as a central case study demonstrating how a religious intellectual reshapes political ethics and governance. The article concludes with a reflection on the challenges posed by recent PBNU conflicts, modernization, and public accountability within the frameworks of al-Ghazali’s thought and secular critiques.